Operative Field Debris Often Rises to the Level of the Surgeon's Face Shield During Spine Surgery: Are Orthopedic Space Suits a Reasonable Solution? - COOK, CHRISTOPHER R. (Int J Spine Surg, 2019)
BACKGROUND: The present study intended to identify debris in the spine surgical field that frequently rises to the level of the surgeon's face during several different elective spine procedures. Unlike other areas of orthopedic surgery where infection risk is of high concern, in spine surgery the surgical team usually uses a nonsterile face mask instead of a protective space suit with a sterile face shield. It is possible that blood or bone burr particles striking the surgeon's face mask represent a potential source of infection if they ricochet back into the operative field. METHODS: We reviewed 46 consecutive, elective spine surgeries between May 2015 and August 2015 from a single-surgeon practice. For each surgery, every member of the surgical team wore sterile (space suit) personal protective equipment. After each procedure, the face shield was carefully inspected by 2 members of the surgical team to identify patient blood, tissue, or bone burr dust present on the face shield. RESULTS: The rate of surgeon face shield debris inspected for each case overall was 38/46 (83%). The rate of first assistant face shield debris inspected per case was 16/46 (35%). The scrub technician had a 0% rate of face mask debris on inspection. The highest debris exposure rates occurred with transforaminal lumbar interbody fusions (100%), open laminectomy and fusions (100%), and anterior cervical discectomy and fusions 43/46 (93%). CONCLUSIONS: There is a high rate of blood and tissue debris contact that occurs during spine surgery, and it is procedure dependent. Spine surgeons may consider using sterile shields particularly in high-risk cases to protect themselves and their patients. LEVEL OF EVIDENCE: 4.